2022
DOI: 10.1177/1357034x221134436
|View full text |Cite
|
Sign up to set email alerts
|

Doing Bodies in YouTube Videos about Contested Illnesses

Abstract: This article is based on an online ethnographic study of Dutch women who use YouTube as a medium to document their contested illness experiences. During 13 months of observations between 2017 and 2019, we followed a sample of 16 YouTubers, and conducted an in-depth analysis of 30 YouTube videos and of 7 interviews. By adopting a ‘praxiographic’ approach to social media, and by utilising insights from phenomenological theory, this study teases out how bodies are ‘done’ in (the making of) these YouTube videos. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Using YouTube as our ‘field’ site (Fullenkamp, 2019; Groenevelt et al, 2022), our study analyses vlogs uploaded to YouTube from 2015 to 2020, with data collection taking place from 2019 to 2020. Vlogs are well-suited for qualitative data analysis as they offer thick descriptions similarly found in in-depth interviewing.…”
Section: Methodsmentioning
confidence: 99%
“…Using YouTube as our ‘field’ site (Fullenkamp, 2019; Groenevelt et al, 2022), our study analyses vlogs uploaded to YouTube from 2015 to 2020, with data collection taking place from 2019 to 2020. Vlogs are well-suited for qualitative data analysis as they offer thick descriptions similarly found in in-depth interviewing.…”
Section: Methodsmentioning
confidence: 99%
“…YouTube provides a variety of sports-related information to the public [32]. Previous research has demonstrated relationships between interest in sports participation and fitness participation motivation [33], exercise practice [34], sports lessons [35], and doing bodies [36] through YouTube engagement. In addition to social science research, studies in sports natural science fields such as sports taping [37] and rehabilitation [38] are also being conducted.…”
Section: Introductionmentioning
confidence: 99%
“…These practices endure as digital technologies shift and develop; sharing one's health experiences with others remains a familiar theme across social media platforms. For example, recent scholarship demonstrates how social media afford different bodily narratives or visibility (Schreiber 2023;Vicari 2021;Groenevelt et al, 2022), and reprieve from the mundane daily challenges of negotiating mental illness and keeping up with one's friends (Hendry, 2020). Much of the labour to communicate care, experience-produced knowledge and community with others is taken up by health (micro-)influencers and content creators.…”
mentioning
confidence: 99%